Regulation of the Switchable Luminescence of Tridentate Platinum(II) Complexes by Photoisomerization - Li, Yongguang; Fei, Yuexuan; Sun, Hongcheng; Yu, Shuangjiang; Liu, Junqiu (Frontiers in Chemistry, 2021)
Organoplatinum (II) complexes are promising candidates for the construction of smart supramolecular materials due to their unique flat structures. This accompanied by intriguing luminescent properties, prompts the molecules to aggregate after external stimuli. Nevertheless, the utilization of photo-responsive subunits to modulate their assemble behaviors and functions are still rarely explored. In this work, azobenzene (azo)-appended tridentate platinum (II) complexes with different linkers have been designed and synthesized. The intermolecular hydrogen bonding, π-π stacking, and metal-metal interactions were finely controlled through the tiny alteration of the linkers, which was found to play a vital role in self-assembly, and photophysical and photoisomerization properties. Some of them exhibited dual emission bands originating from metal-perturbed triplet intraligand (3IL) and metal-metal to ligand charge transfer (3MMLCT) excited states due to the different intermolecular interactions. Based on this, the manipulation of switchable luminescence as well as the controllable morphologies have been realized by photoisomerization.